Contingencies influencing management accounting practice: A yemen-based empirical study / Ahmed Abdullah Saad Al-Dhubaibi ... [et al.] - Al-Dhubaibi, Ahmed Abdullah Saad; Abdul Rahman, Ibrahim Kamal; Haniff, Mohd Nizal; Mohd Sanusi, Zuraidah (Faculty of Accountancy, 2014)
significant number of management accounting studies have observed various levels of management accounting practice (MAP) adoption. Although academicians and practitioners have argued that advanced MAPs create value and improve the performance of their adopters, researchers have determined that traditional MAPs remain dominant in the market. This study aims to contribute to the extant body of knowledge on this topic by exploring the level of MAP adoption in Yemen and by examining the effect of certain external (environmental) and internal (organisational) factors on the level of MAP advancement. The sample firms include large firms that operate in various economic sectors in Yemen, such as manufacturing, financial, natural resources extraction and service, as well as medium and small firms to achieve sufficient sample size. The International Federation of Accountants (IFAC) framework on management accounting stages is used to classify the levels of MAP advancement. Competition level and structure type (level of delegation) significantly explain the variations in MAP advancement levels among firms in Yemen. A higher degree of competition and amount of delegations can drive firms to adopt more sophisticated MAPs. These results improve our understanding of why some firms invest in upgrading their management accounting systems and target best practices, whereas other firms tend to continue using traditional MA tools.